Effectiveness of Comprehensive Nursing Education On Medication Adherence and Self-Care Management In Heart Disease Patients: A Quasi-Experimental Study - Kiki Fajar Nurhidayah; Ninuk Dian Kurniawati; Arina Qona’ah (Jurnal Ners, 2026)
Medication adherence and self-care management are essential components in improving clinical outcomes among patients with heart failure. However, inadequate adherence and poor self-care remain major challenges in nursing practice. Objective this study aimed to evaluate the effectiveness of comprehensive education in improving medication adherence and self-care management among patients with heart failure. Methods this study employed a quasi-experimental design with a pre-test–post-test control group approach. A total of 40 outpatients with heart failure were recruited using purposive sampling and proportionally assigned to intervention and control groups. The intervention group received comprehensive education consisting of educational booklets, videos, and teach-back sessions over two weeks, while the control group received standard care. Medication adherence was assessed using the Morisky Medication Adherence Scale (MMAS-8), and self-care was measured using the Self-Care of Heart Failure Index (SCHFI). Data were analyzed using the Wilcoxon Signed-Rank Test for within-group comparisons and the Mann–Whitney U Test for between-group comparisons, with a significance level of p < 0.05. Results the intervention group demonstrated a significantly greater improvement in medication adherence than the control group (p = 0.001). Significant improvements were also observed in all SCHFI dimensions, including self-care maintenance (p = 0.002), self-care management (p = 0.001), and self-care confidence (p = 0.003), compared with the control group. Conclusion comprehensive education significantly improves medication adherence and self-care management among patients with heart failure. Integrating educational booklets, audiovisual media, and teach-back techniques into nursing practice may enhance patients' self-management abilities and support better clinical outcomes.